Características da pulverização produzida por pontas Yamaho da série 'D' - Ramos, Hamilton Humberto; Matuo, Tomomassa; Bernardi, José Augusto; Maziero, José Valdemar Gonzalez (FapUNIFESP (SciELO), 2002)
This study evaluated the characteristics of spray produced by Yamaho nozzle tip'D'series. The droplet size of nozzle tips D3, D4, D5, D6 and D8 were evaluated at 703, 1.050, 1.406, 1.758, 2.110, 2.461 e 2.813 kPa pressures (100, 200, 250; 350, e 400 psi) by means of laser equipment, as well as the flow rate of nozzle tip at the pressures of 702, 1.125, 1.406, 1.828, 2.110, 2.532 e 2.813 kPa (100, 160, 200, 260,300; 360 e 400 psi) which were compared with values indicated by manufacturer. The droplet produced at all pressures presented a very fine spray, which in agriculture may promote losses by evaporation and drift. For all nozzle tips, except D8 in pressures 1.828, 2.532 e 2.813 kPa, the difference between the observed flow rate indicated by the manufacturer was higher than 5%. The paper demonstrates that the nozzle tip tested, in spite of not having uniform flow rate, may promote the contamination of spray operator and environment due to the droplet spectrum produced.
Characteristics of spray produced by Yamaho nozzle 'D' series
Keywords: Pesticides; Sprayers; Spraying nozzle; pesticide; spray